2021
DOI: 10.1108/cg-08-2020-0329
|View full text |Cite
|
Sign up to set email alerts
|

Board’s financial expertise and corporate social responsibility disclosure in China

Abstract: Purpose This study aims to investigate the impact of the board’s financial expertise (BFE) on corporate social responsibility (CSR) disclosure in China. Design/methodology/approach Using a sample of Chinese listed firms from 2009-2016 (making 3272 firm-year observations), this study uses the generalized method of moments (GMM) and panel data estimation techniques. Findings Using the resource dependence theory, the findings of this study are twofold. First, the is positively associated with the disclosure l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 90 publications
(171 reference statements)
0
29
1
Order By: Relevance
“…In companies with majority shareholders ownership, CSR information is more likely to be disclosed when the board, audit committee and the ownership concentration are all positive factors (Fallah & Mojarrad, 2019). Thus, by replacing financial background executives, the previous company will be unable to make the same strategic decisions, while the new executives may be less familiar with financial information, capital markets operations, and long-term strategies than the previous executives (Naheed et al, 2021). As a result, the focus may be on short-term performance for the sake of winning the trust of short-term shareholders and investors and reducing investments in CSR after a change of senior management (Rashid et al, 2020;Rokhayati et al, 2021).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In companies with majority shareholders ownership, CSR information is more likely to be disclosed when the board, audit committee and the ownership concentration are all positive factors (Fallah & Mojarrad, 2019). Thus, by replacing financial background executives, the previous company will be unable to make the same strategic decisions, while the new executives may be less familiar with financial information, capital markets operations, and long-term strategies than the previous executives (Naheed et al, 2021). As a result, the focus may be on short-term performance for the sake of winning the trust of short-term shareholders and investors and reducing investments in CSR after a change of senior management (Rashid et al, 2020;Rokhayati et al, 2021).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…In a variety of studies (Cao et al, 2006;Cust odio & Metzger, 2014;Dwekat et al, 2020;Fallah & Mojarrad, 2019;Naheed et al, 2021;Qa'dan & Suwaidan, 2019;Rashid et al, 2020;Shen et al, 2017), it has been found that changes of top management in the organization not only cause major strategic changes, but also distress the association between the company and its internal and external stakeholders.…”
mentioning
confidence: 99%
“…The existing evidence (e.g., Kothari et al, 2009;Cormier and Magnan, 2014;Leuz and Wysocki, 2016;Dyer et al, 2017;El-Diftar et al, 2017;Naheed et al, 2021) suggests that corporate disclosure, which covers several topics including, for example, forward-looking, corporate social responsibility, and risk, benefits companies as it improves corporate transparency and thus reduces information asymmetries. Based on prior literature (e.g., Linsley and Shrives, 2005), risk disclosure practises should result in improving corporate transparency.…”
Section: Introduction and Research Backgroundmentioning
confidence: 99%
“…The impact of corporate governance on firms' fundamentals is also debated among researchers. The board characteristics across different countries also impact the fundamental characteristics of the firm (Muhammad et al, 2020;Naheed et al, 2021;Ullah et al, 2021). Compliance with the corporate governance mechanism enhances the monitoring of managerial activities and reduces the conflict between agent and principal.…”
Section: Contextual Settings Of the Studymentioning
confidence: 99%
“…Accordingly, as per the institutional settings, managers deviate from the best operating practices to engage in REM. The general outlook is that as accounting regulations are stricter after the implementation of the Sarbanes-Oxley Act, firms are more involved in REM activities (Naheed et al, 2021). The literature on REM is evolving and studies from different institutional settings present mixed results.…”
Section: Introductionmentioning
confidence: 99%